2010
DOI: 10.1186/ar3086
|View full text |Cite
|
Sign up to set email alerts
|

The delivery of evidence-based preventive care for older Americans with arthritis

Abstract: IntroductionPrevious research suggests patients with rheumatoid arthritis (RA) may receive suboptimal care with respect to preventive tests and services. We evaluated the proportion of older Americans with RA, psoriatic arthritis (PsA), and osteoarthritis (OA) receiving these services and the specialty of the providers delivering this care.MethodsUsing data from 1999 to 2006 from the Medicare Chronic Conditions Warehouse, we identified persons age >/= 65 in the national 5% sample. Over the required five-year o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 38 publications
2
34
2
Order By: Relevance
“…This is in keeping with previous findings from our cohort and others reporting less than optimal preventive screening of individuals with RA (24, 25). It could be suggested that initial lower lipid levels in RA vs non-RA subjects may lead to the lower likelihood of subsequent reassessment of lipid levels in RA.…”
Section: Discussionsupporting
confidence: 93%
“…This is in keeping with previous findings from our cohort and others reporting less than optimal preventive screening of individuals with RA (24, 25). It could be suggested that initial lower lipid levels in RA vs non-RA subjects may lead to the lower likelihood of subsequent reassessment of lipid levels in RA.…”
Section: Discussionsupporting
confidence: 93%
“…40 Current literature suggests that rheumatologists do not routinely address the need for vaccination prior to starting therapy with biologic DMARDs, and for the most part, recommended vaccines are used infrequently among patients with RA. [41][42][43] While our study addressed two of the most important recommended vaccines, it should be noted that a newly available protein-conjugate vaccine for pneumococcus is recommended for patients with RA in the USA and other regions. 44 45 The pneumococcal conjugate vaccine (PCV-13) provides protection against 13 serotypes, 12 of which are contained within the PPSV-23 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the screening for the detection of breast cancer (a cancer which is not more frequent in rheumatoid arthritis than in the general population) by mammography might be less frequently performed in women with rheumatoid arthritis [50][51][52]. Most of the rheumatologists consider now that it is their responsibility, at least, to assess the screening for comorbidities and for risk factor of comorbidities and thereafter to liaise with the appropriate specialist for the treatment phase [33].…”
Section: Management Of Comorbidities In Rheumatoid Arthritismentioning
confidence: 99%